Impact of Servitized Corporate Models in Providing A Competitive Edge to The Manufacturing Industry - Sakib, S M Nazmuz (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2025)
This document reviews the impact of servitization on manufacturing companies' corporate models. It discusses how product-centric firms can transition to service-oriented models by incorporating software services into their offerings. The literature review covers key concepts like servitization, corporate models, value propositions, and organizational changes required. An analytical model is developed to assess the case company's servitization efforts through its CSA software platform. Empirical data from interviews finds the value proposition was inadequate due to inability to demonstrate CSA's benefits. Organizational changes were not properly implemented, leading to lack of resources allocated. The study shows the importance of organizational factors like culture, communication, and strategy alignment in enabling servitization.